Effect of Lateral Crural Procedures on Nasal Wall Stability and Tip Aesthetics in Rhinoplasty. (18th January 2021) - Abdelwahab, Mohamed; Patel, Priyesh; Kandathil, Cherian K.; Wadhwa, Harsh; Most, Sam P.
Abstract : Objectives/Hypothesis: To evaluate the lateral nasal wall stability, nasal function, and cosmesis when creating an aesthetically pleasing nasal tip subunit utilizing lateral crus (LC) altering procedures. Study design: Retrospective cohort. Methods: In this retrospective cohort study, cosmetic rhinoplasty patients undergoing LC procedures with available lateral wall insufficiency (LWI) scores were included. An LWI grading system was used to evaluate internal (zone 1) and external (zone 2) nasal valves objectively. Secondarily, Nasal Obstruction Symptom Evaluation (NOSE) Score, Visual Analog Scale (VAS) and Standardized Cosmesis and Health Nasal Outcomes Survey (SCHNOS) results were evaluated. Based on the LC intervention, the cohort was divided into six groups: lateral cural strut graft (LCSG), mini‐LCSG, lateral crural overlay (LCO) with and without additional support, cephalic trimming, and cephalic turn‐in flaps. Results: Subjects undergoing LCO with and without support, LCSG, and mini‐LCSG showed significant improvement in zone 1 LWI ( P = .042, P = .041, P < .001, and P < .001, respectively), while cephalic trimming and turn‐in/hinged flaps had no effect. Subjects undergoing LCO with support and LCSG showed significant improvement in zone 2 LWI ( P = .022, P = .004), while LCO without support, mini‐LCSG, cephalic trimming, and turn‐in flaps showed no effect on LWI. The SCHNOS‐C and VAS‐C showed significant improvement in all subgroups ( P < .05) when comparing pre‐ to postoperative values. Alar‐spanning sutures did not significantly change zone 1 scores but did conceal zone 2 improvements in LCSG and LCO with support groups. Conclusions: Selected LC procedures are robust techniques for improving tip cosmesis independently without compromising nasal lateral wall stability. Some LC procedures can improve nasal valves patency in tip surgery. Laryngoscope, 131:E1830–E1837, 2021